POTENSI KESESUAIAN MANGROVE SEBAGAI DAERAH EKOWISATA DI DUSUN TANJUNG TEDUNG SUNGAI SELAN BANGKA TENGAH - Susi Susi; Wahyu Adi; Suci Puspita Sari (Department of Aquatic Resources Management, Faculty of Agriculture, Fisheries, and Biology, University of Bangka Belitung, 2018)
Tanjung Tedung Coastal Coast is located in Tanjung Pura Village, Sungai Selan Subdistrict, Bangka Tengah. Regency which has the potential to be developed into a mangrove ecowista area, because almost along the coastal area is overgrown with ecosystem mengrove. This study aims to identify the potential of mangrove ecosystems and calculate the Tourist Compatibility Index (IKW) potential of mangrove area as ecotourism area of mangrove. The data were collected from March to April 2018 in Tanjung Tedung Coastal Coast. The research method used is Purposive Sampling. Research area taken as many as 3 stations. The data analysis is based on tourism conformity index matrix (IKW). Data of mangrove tourism conformity parameter consisting of: mangrove thickness, mangrove density, mangrove species, tidal and biota object. The result of measurement of mangrove tourism match parameters are thickness at station I worth 303,57 m, station II worth 366,57 m and station III worth 1,061,44 m. Density of station I with value 0.11 ind / m². Station II worth 0.10 ind / m² and station III with value 0.16 ind / m². Found 9 Species of mangroves and other biota such as: fish, shrimp, crab, molluscs, reptiles, birds and other biota. The result of conformity analysis to be used as ecotourism area with IKW value of station I worth 78.95% with Appropriate category. Furthermore at station II IKW value is 78.95% with Appropriate category. and station III got the value of IKW worth 96.05% with category Very